Modelo de classificação para destinação de dejetos suínos - Machado , Luana do Pilar (2021)
The present study aims to propose a classification model to assist the rural producer in decision making about the destination of swine manure. For this, visits were made to 20 rural properties with swine production (up to 3000 unity) and a form with objective questions was applied. After tabulation of the data, three destination situation swere defined. Such situation are: Destination 1 (D1) "Maintain current situation", Destination 2 (D2) "Sell swine waste" and Destination 3 (D3) "Deploy a biodigester". Then, variables were chosen subdivided into three macro areas: economic, social and environmental. Statistical correlation tests were performed to validate one of the variables applied in the three situations under study. It can be observed that the social macro area has no correlation between the other variables and there is no statistical difference in the study. Therefore, it was necessary to redefine the variables to use the classification model, where they were subdivided into two macro areas: economic and socio-environmental. The classification model will present the best option for the destination of swine waste based on the data entered and according to the characteristics of each rural property. Intended, specific inputs that supply the classification model were defined. Based on this, the model performs simulations for the three types of destinations, taking into account the stipulated variables and defining the best destination for swine manure (output). The model is a tool that helps to assert the destination of swine manure and contributes to the activity on rural properties. In addition to providing information to the rural producer about the costs and revenues involved with the handling of swine manure.